Travel Cost Method for Valuing Destinations and Atractions: The Paradox of Muslim-Friendly Tourism - Suteja Wira Dana Kusuma; Elsa Yulandri; Vemy Suci Asih; Endah Trihayuningtyas; Mila Badriyah (Centre For Tourism Planning and Development, 2026)
This study compares the economic value of two tourist sites: Al-Jabbar, a single attraction, and the City of Semarang (CoS), a multi-attraction site, using the Travel Cost Method (TCM). The results show a significant difference in consumer surplus, with CoS generating about Rp. 6,289,308 per visit, far exceeding Al-Jabbar's Rp. 801,282 per visit. This highlights CoS's broader appeal and diverse offerings, attracting more visitors and maximising economic benefits. Al-Jabbar visitors are more sensitive to travel cost changes, affecting their visit frequency, while CoS visitors show lower sensitivity, likely due to the variety of attractions. The study also reveals a paradox in Muslim Friendly Tourism (MFT) services. At Al-Jabbar, MFT considers a decrease in visit frequency, suggesting limited appeal, whereas at CoS, MFT has no significant impact, possibly due to the destination's diverse attractions. These insights are crucial for destination management and tourism development.